Die Rolle von Finanzinvestoren beim Umbau der deutschen Ökonomie - Beckmann, Martin (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
The German economy, for long time characterised by a bank based financial system with capital and personal linkages between the main financial and industrial economies, has been transformed since the 1990s to a market orientated economy. Particularly German banks and insurance companies sold many of their stakes in industrial companies. This gap has been filled by new financial investors like pension funds, hedge funds and private equity.